Rediagnosis of the squat lobster genus Gastroptychus Caullery, 1896, with a new genus Sternostylus and a new family Sternostylidae (Crustacea: Decapoda: Anomura: Chirostyloidea) - Baba, Keiji; Ahyong, Shane T.; Schnabel, Kareen E. (Zootaxa, 2018)
The chirostyloidean squat lobster genus Gastroptychus Caullery, 1896 is revised and is split into two genera: Gastroptychus sensu stricto (type species, Ptychogaster spinifer A. Milne-Edwards, 1880) and Sternostylus new genus (type species, Ptychogaster formosus Filhol, 1884). Gastroptychus sensu stricto, is restricted to nine species with a sternal plastron, at sternite 3, abruptly demarcated from the preceding sternites (excavated sternum) by a distinct step forming a well-defined transverse or concave anterior margin at the articulation with maxillipeds 3, the maxillipeds 3 widely separated, with the distal parts accommodated in the excavated sternum between the left and right maxillipeds 3 when folded, and the P2–4 dactyli with the terminal spine demarcated by a suture. Sternostylus new genus, represented by 12 species, has the sternite 3 anteriorly bluntly produced medially and steeply sloping anterodorsally to the anterior sternite, with a pair of spines directly behind the anterior margin, the left and right maxillipeds 3 adjacent, and the P2–4 dactyli ending in an indistinctly demarcated corneous spine. The above-mentioned characters of Gastroptychus are consistent with Chirostylidae sensu stricto. Published molecular phylogenies indicate, however, that Sternostylus is the sister group to all the other Chirostylidae, and is designated the type genus of a new family, Sternostylidae.